2000
DOI: 10.1016/s0928-8244(00)00136-x
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcal serogroup C-specific IgG antibody responses and serum bactericidal titres in children following vaccination with a meningococcal A/C polysaccharide vaccine

Abstract: In the UK, a co-ordinated series of phase II studies is being undertaken with meningococcal serogroup C conjugate (MCC) vaccines. The use of meningococcal A/C polysaccharide (MACP) vaccines in control arms in young children has been avoided because of the well recognised short comings of these vaccines. Following a cluster of serogroup C disease centred on a day nursery, intervention by MACP vaccination was performed as an outbreak control measure. Using this cohort, serogroup C-specific IgG ELISA and serum ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
(36 reference statements)
1
15
0
Order By: Relevance
“…This is also supported by the vaccine effectiveness reported following a mass immunization campaign against menC disease in Quebec, where the effectiveness was 41% for ages 2 to 9 years (12). Our data for menC are also similar to those reported in a previous study of bivalent polysaccharide in young children in the United Kingdom (10). A small French study performed with older children (ages, 3 to 13 years) and with a single dose of tetravalent polysaccharide demonstrated that all 21 children responded, as measured by a Նfourfold increase in the SBA titer pre-to post vaccination for all four serogroups (11).…”
Section: Discussionsupporting
confidence: 89%
“…This is also supported by the vaccine effectiveness reported following a mass immunization campaign against menC disease in Quebec, where the effectiveness was 41% for ages 2 to 9 years (12). Our data for menC are also similar to those reported in a previous study of bivalent polysaccharide in young children in the United Kingdom (10). A small French study performed with older children (ages, 3 to 13 years) and with a single dose of tetravalent polysaccharide demonstrated that all 21 children responded, as measured by a Նfourfold increase in the SBA titer pre-to post vaccination for all four serogroups (11).…”
Section: Discussionsupporting
confidence: 89%
“…The SBA response to the booster MCC-TT vaccine was higher than the response to primary immunization and the response in naive toddlers receiving MCC-TT vaccine at this age (27a). The antibody response to the booster MACP vaccine was greater than in naive children given this vaccine (7,20,22), confirming the successful induction of immunologic memory. The presence of memory is sufficient for long-term protection following administration of Hib conjugate vaccines (5,28) and is expected to be sufficient after administration of MCC vaccines, although the high incidence of MenC disease in adolescence (25) means that a longer duration of protection is required.…”
Section: Discussionmentioning
confidence: 60%
“…Sera were tested using standardized complement-mediated serum bactericidal assays against three MenC strains described previously (7,26). The complement source was pooled baby rabbit serum (Pelfreeze Biologicals).…”
Section: Methodsmentioning
confidence: 99%
“…For toddlers with a postprimary SBA titer of Ͻ128, 90% had a postbooster titer of Ն128, compared with only 8% of age-matched naïve controls given a full 50-g dose of C polysaccharide (8). This difference in response confirms the induction of immunological memory in the MCC vaccines despite postprimary SBA antibody levels in the equivocal range.…”
Section: Discussionmentioning
confidence: 70%